1999
DOI: 10.5144/0256-4947.1999.453
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Skin Diseases at King Khalid National Guard Hospital: A 12-Month Prospective Study

Abstract: . Jeddah is the major city in the Western region, with an approximate population of two million. The city is located on the Red Sea, and has a hot climate, with daily temperatures ranging from 15-43°C. throughout the year, with high humidity at times and only occasional rainfall. The King Khalid National Guard Hospital is one of the major government hospitals in the region catering for national guard military personnel and their families, as well as non-national guard patients. The hospital offers secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…Our results have shown that infections, eczema/dermatitis, pilosebaceous disorders, pigmentary lesions and hair disorders ranked among the top 5 skin diseases (Figure 2). The results of this study are comparable to those of other studies from Riyadh, Abha, Jouf, Hail, Jeddah, Najran, the Eastern Province and the Asir region of Saudi Arabia 235891213. These studies have reported a similar pattern of skin diseases in Saudi patients.…”
Section: Discussionsupporting
confidence: 89%
“…Our results have shown that infections, eczema/dermatitis, pilosebaceous disorders, pigmentary lesions and hair disorders ranked among the top 5 skin diseases (Figure 2). The results of this study are comparable to those of other studies from Riyadh, Abha, Jouf, Hail, Jeddah, Najran, the Eastern Province and the Asir region of Saudi Arabia 235891213. These studies have reported a similar pattern of skin diseases in Saudi patients.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was similar with that of other studies. 5,6 The prevalence of various skin diseases varies according to geographical area and usually related to many factors including race, environment and socioeconomic factors of populations. In the present study, we found that eczema (23.7%) was the commonest skin disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to that of others. 3,[6][7][8][9][10][11] Fungal infections were the second largest group of disorders seen in 15.5% of patients. The warm and highly humid climate of the country contributed to the higher proportion of fungal infections in this population.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The incidence of vitiligo at King Khalid University Hospital (KKUH), Riyadh, Saudi Arabia was 2.5% for the period from [1985][1986][1987][1988][1989][1990], the majority (96.1%) were Saudis, (2) the disease has a worldwide prevalence ranging from 0.5% to 2%. (3) It can affect any age of both sex. (4,5) Vitiligo is an ancient disease as mentioned in the Holy Quran when stating 'Eesa that he cures the born blind and the patient with Baras (vitiligo).…”
Section: Introductionmentioning
confidence: 99%